Associations of one-carbon metabolism, related B-vitamins and ApoE genotype with cognitive function in older adults: identification of a novel gene-nutrient interaction - Cunningham, Conal (My University, 2025)
Background: The role of one-carbon metabolism and related B-vitamins in cognitive function in ageing is well-documented, particularly for folate and vitamin B12, with vitamin B6 and riboflavin receiving much less attention. ApoE is a well-established genetic risk factor for Alzheimer’s disease, but the role of B-vitamins in modifying this risk remains largely unexplored. We examined associations between folate, B12, B6, riboflavin, and cognitive function in older adults, including interactions with the ApoE ε4 genotype. Methods: Community-dwelling older adults (≥ 60 years) from the Trinity-Ulster-Department of Agriculture (TUDA) study were stratified as ApoE ε4 carriers (ε3/ε4 and ε4/ε4 genotypes; n = 1205) or non-ε4 carriers (n = 3348). Cognitive function was assessed using the Repeatable Battery for Assessment of Neuropsychological Status (RBANS), the Frontal Assessment Battery, and the Mini-Mental State Examination. Logistic regression models were used to evaluate the association between cognitive dysfunction (defined as RBANS score < 80) and a range of variables, including biomarkers of folate, vitamins B12, B6, and riboflavin status, plasma homocysteine levels, and ApoE ε4 genotype. Results: Lower status of vitamin B12 (holotranscobalamin; adjusted odds ratio (ORadj 1.30; 95% CI: 1.08–1.58, p = 0.007), vitamin B6 (ORadj 1.37; 95% CI: 1.12–1.67, p = 0.002), riboflavin (ORadj 1.73; 95% CI: 1.44–2.09, p < 0.001), and higher plasma homocysteine (ORadj 1.50; 95% CI: 1.22–1.83, p < 0.001) were each associated with higher risk of cognitive dysfunction. The ApoE ε4 genotype interacted adversely with low B12 status (p = 0.030) and elevated homocysteine (p = 0.008) in relation to cognitive outcomes. Conclusions: Low status of vitamin B12, B6, riboflavin, and/or elevated homocysteine were each associated with a greater risk of cognitive dysfunction. A novel interaction between ApoE ε4 and low B12 or higher homocysteine was associated with an increased risk of cognitive dysfunction. Improving B-vitamin status may have important public health benefits for dementia prevention. Further investigation, ideally in the form of randomised trials, is however required to demonstrate a causative relationship and confirm whether intervention with B-vitamins can confer a beneficial effect in maintaining better cognitive health in at-risk older people.
PUBLISHED
Cited by: 0
Keywords: Cognitive function; Folate; Vitamin B12; Vitamin B6; Riboflavin; Homocysteine; Apolipoprotein E (ApoE ε4); One-carbon metabolism; Trinity-Ulster-Department of Agriculture (TUDA)